Allopregnanolone alters follicular and luteal dynamics during the estrous cycle - Joana Antonela Asensio; Antonella Rosario Ramona Cáceres; Laura Tatiana Pelegrina; María de los Ángeles Sanhueza; Leopoldina Scotti; Fernanda Parborell; Myriam Raquel Laconi (BMC, 2018)
Abstract Background Allopregnanolone is a neurosteroid synthesized in the central nervous system independently of steroidogenic glands; it influences sexual behavior and anxiety. The aim of this work is to evaluate the indirect effect of a single pharmacological dose of allopregnanolone on important processes related to normal ovarian function, such as folliculogenesis, angiogenesis and luteolysis, and to study the corresponding changes in endocrine profile and enzymatic activity over 4 days of the rat estrous cycle. We test the hypothesis that allopregnanolone may trigger hypothalamus - hypophysis - ovarian axis dysregulation and cause ovarian failure which affects the next estrous cycle stages. Methods Allopregnanolone was injected during the proestrous morning and then, the animals were sacrificed at each stage of the estrous cycle. Ovarian sections were processed to determine the number and diameter of different ovarian structures. Cleaved caspase 3, proliferating cell nuclear antigen, α-actin and Von Willebrand factor expressions were evaluated by immunohistochemistry. Luteinizing hormone, prolactin, estrogen and progesterone serum levels were measured by radioimmunoassay. The enzymatic activities of 3β-hydroxysteroid dehydrogenase, 3α-hydroxysteroid oxidoreductase and 20α-hydroxysteroid dehydrogenase were determined by spectrophotometric assays. Two-way ANOVA followed by Bonferroni was performed to determine statistical differences between control and treated groups along the four stages of the cycle. Results The results indicate that allopregnanolone allopregnanolone decreased the number of developing follicles, while atretic follicles and cysts increased with no effects on normal cyclicity. Some cysts in treated ovaries showed morphological characteristics similar to luteinized unruptured follicles. The apoptosis/proliferation balance increased in follicles from treated rats. The endocrine profile was altered at different stages of the estrous cycle of treated rats. The angiogenic markers expression increased in treated ovaries. As regards corpora lutea, the apoptosis/proliferation balance and 20α-hydroxysteroid dehydrogenase enzymatic activity decreased significantly. Progesterone levels and 3β-hydroxysteroid dehydrogenase enzymatic activity increased in treated rats. These data suggest that allopregnanolone interferes with steroidogenesis and folliculogenesis at different stages of the cycle. Conclusion Allopregnanolone interferes with corpora lutea regression, which might indicate that this neurosteroid exerts a protective role over the luteal cells and prevents them from luteolysis. Allopregnanolone plays an important role in the ovarian pathophysiology.